Association of Naples Prognostic Score with anemia in cancer survivors: a study based on NHANES database - Wu, Qian; Cai, Junhui; Li, Juan; He, Guoping; Yang, Xuefeng; Chen, Lulu; Sun, Yupeng; Gou, Xiaoxia (Frontiers in Oncology, 2025)
BackgroundAnemia is a prevalent issue among cancer survivors, which greatly affects their quality of life and overall prognosis. The Naples Prognostic Score (NPS), an inflammation-based prognostic tool, is increasingly acknowledged for its potential in predicting clinical outcomes. This study aims to assess the correlation between anemia status, prognosis, and NPS in cancer survivors.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) database spanning from 2003 to 2018, along with death data from the National Death Index (NDI) up to December 31, 2019. A total of 80,312 participants were included, of whom 4,260 were identified as cancer survivors. After applying rigorous exclusion criteria for missing variables, 3,143 participants were retained in the final analysis. NPS was calculated using serum albumin (ALB), total cholesterol (TC), neutrophil to lymphocyte ratio (NLR), and lymphocyte to monocyte ratio (LMR). After adjusting relevant confounding factors, weighted univariable and multivariable logistic regression were utilized to calculate the odds ratios (OR) and 95% confidence intervals (CI). Kaplan-Meier (KM) curves and Log-rank test were employed to compare survival differences among the three patient groups, while Cox proportional regression was utilized to estimate hazard ratio (HR) and 95% CI. Additionally, subgroup analyses were performed to assess the consistency of the outcomes.ResultsUnivariable and multivariable analyses indicated positive correlation between NPS and anemia in cancer survivors (P < 0.05). When NPS was treated as continuous variable, crude model showed that higher NPS scores were linked to higher likelihood of anemia in cancer survivors (OR: 1.77, 95% CI: 1.55 - 2.02; P < 0.001), and this association remained significant even after adjusting for all confounding variables (OR: 1.66, 95% CI: 1.45 - 1.90; P < 0.001). Moreover, with Q1 (score = 0) as the reference category, the analysis demonstrated positive association between NPS and the prevalence of anemia in cancer survivors, regardless of whether the model was crude or fully adjusted (P < 0.001). KM analysis indicated that the decline in overall survival from all causes and other causes was significantly more pronounced among anemic cancer survivors in the Q3 (score = 3 or 4) group (P < 0.05). After accounting for all confounding factors, individuals with the highest NPS had HR of 2.46 (95% CI: 1.81 - 3.34) for all-cause mortality. However, there were no significant differences in mortality trends related to cardiovascular or cancer causes (P > 0.05). Subgroup analyses and sensitivity analysis revealed no statistically significant interactions (P for interaction < 0.05).ConclusionsThe study highlights the correlation between higher NPS and an increased prevalence of anemia in cancer survivors, indicating that NPS may serve as a valuable tool for assessing the prognosis of cancer survivors in clinical practice and for guiding interventions aimed at mitigating anemia-related complications.